Commentary: trends in interests of new public health students concerning environmental health - Shendell, Derek G.; Aggarwal, Juhi (Frontiers in Education, 2024)
Introduction: This paper was based on data from the core course in environmental health (EH) for master’s in public health students at Rutgers School of Public Health (SPH), Rutgers Biomedical and Health Sciences at Rutgers, The State University of New Jersey (NJ). Methods: The multi-part poll or survey of students was in the first module (two weeks) of the course’s eight module organization on Rutgers Canvas Learning Management System. We collected data every time the first author led this course section during the three academic semesters of each calendar year 2015-2023 (excluding winter 2022-summer 2023 due to grants buyout during COVID-19 pandemic). Results: Data suggested interesting trends and changes in geographic levels of interest over time for EH. When examining interests separately for urban EH and rural EH, the trend was toward approximately equal interests in local, county and state levels (lower than national level—U.S. or student’s home country/nation—but higher than global level). This is where many EH job opportunities are located. Overall, 95% of students reported they believed climate change is real, and 95% of students agreed (“yes”) human activities including combustion sources of pollution contribute to climate change. No one stated “no;” the rest were not sure at the time. Discussion: These insights from new public health students across majors/concentrations in NJ could inform other accredited SPH across the U.S. and in other nations to help plan future versions of core courses in EH or SPH-wide integrated core courses in compliance with required competencies for accreditation.